2015
DOI: 10.1016/j.otsr.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The posterior condylar offset ratio and femoral anatomy in anterior versus posterior referencing total knee arthroplasty

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…However, the mean postoperative PCO was greater in the AR group. Almeida et al reported that there was no difference in the postoperative PCO and PCOR between the AR and PR groups [7]. In the previous study, the mean postoperative PCO was 27.4 mm in the AR group and 27.7 mm in the PR group (p = 0.32).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, the mean postoperative PCO was greater in the AR group. Almeida et al reported that there was no difference in the postoperative PCO and PCOR between the AR and PR groups [7]. In the previous study, the mean postoperative PCO was 27.4 mm in the AR group and 27.7 mm in the PR group (p = 0.32).…”
Section: Discussionmentioning
confidence: 81%
“…On the other hand, preservation of the posterior condylar offset (PCO) and posterior condylar offset ratio (PCOR) was reported to be related to the degree of maximal flexion after TKA [7][8][9][10][11][12][13][14][15][16]. The PCO or PCOR after TKA could differ based on the referencing system used.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to posterior clearance, PCO and PCO ratio (PCOR) are important outcome measures of knee joint function 3,10,11 and these values have been reported to increase postoperatively. 12,13 Almeida et al 13 reported that postoperative PCOR did not differ between the AR and PR methods, showing a significant increase in both cases. For PCO, opinions are divided as to whether it influences ROM 3,6,7,11,14 or not.…”
Section: Discussionmentioning
confidence: 95%
“…Lateral radiographic images of the knee were analyzed on our picture archiving and communication system (PACS, SECTRA Inc., Shelton, CT, USA) and measured for posterior condylar offset (PCO), posterior condylar offset ratio (PCOR), and tibial slope as described by Mont, Almeida, and Bernhardson, respectively. [12][13][14] Soft-tissue envelope thickness in the prepatellar and pretubercle region was calculated by the methods used by Watts and colleagues. 15 The AP radiograph was then evaluated for joint line elevation using the femoral epicondylar landmarks, as outlined by Servien et al 16 One author (C.M.H.)…”
Section: Methodsmentioning
confidence: 99%